Greening and Garden arrangement based on ecotourism at the Faculty of Agriculture, Khairun University - Nurfadhillah Arif; Fadila Tamnge (Universitas Muhammadiyah Palembang, 2024)
Campus park are one of the important elements in the college area. The presence of campus park as green open spaces can be used as a means of supporting lectures. Garden arrangements in campus park at the Faculty of Agriculture, Campus II, Gambesi, Khairun University, Ternate can add beauty, provide comfort and a fresh impression and can provide benefits for the environment and humans. The aim of this PKM activity is to identify the needs and desires of the campus community; both lecturers and students in designing campus parks and preparing campus park design concepts. PKM activities are divided into 5 stages, namely the preparation stage, survey of user needs, design, garden arrangement, and evaluation. The identified needs of park users include campus park facilities and conditions, vegetation and accessibility. The campus park designed by the PKM team does not change the shape of the existing park. Some of the things the team did were revamping the existing garden and adding several types of flowers and agricultural plants. The aim is to give a beautiful impression and produce food sources as part of the Agro-edutourism. The garden arrangement at Campus II of the Faculty of Agriculture, Khairun University was carried out by creating a park design without changing its original shape by rearranging the existing vegetation and adding several types of plants.